A Morphological Study in Group Online Communication: Word - Formation Processes among College Students in a WhatsApp Group - I Putu Yoga Laksana; Gary P. Boyce (Politeknik Negeri Bali, 2020)
The emergence of group online communication provides various patterns in using language, especially in written text. In the process, teenagers and adult learners who frequently use online communication produce new vocabularies, spelling modifications, symbols, and emoticons in their online written communication. This study focusses on the word-formation processes used in written online communication especially during usage of a WhatsApp Group (WAG). The study aims at finding types of word-formation processes that emerged in WAG. Collected data was examined empirically to understand the characteristics of WAG users and their patterns in forming words. A descriptive method and data collected from 30 chats were gathered from WAG consisting of students attending Mahasaraswati University in Bali. The study analyzed 336 words and classified them into the appropriate word-formation processes (Yule, 2010). The study found three predominant types of processes used by WAG users: borrowing, multiple processes, clipping, and three other processes included acronym, blending, and miscellaneous (not stipulated in his theoretical backing (see table 6)), which were used less by WAG users. Changing words into shorter or simpler forms and borrowing words from other languages were some strategies used by the users of WAG to accelerate the production of text or chat. These appear to be the reasons why users mainly generated these three most types of word-formation processes in WAG. The investigation has presented a diversity of word-formation processes used in WAG. In turn, this diversity may cast light on the creativity of online group communication language usage.